5x-11=9-(4-14)

Simple and best practice solution for 5x-11=9-(4-14) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-11=9-(4-14) equation:


Simplifying
5x + -11 = 9 + -1(4 + -14)

Reorder the terms:
-11 + 5x = 9 + -1(4 + -14)

Combine like terms: 4 + -14 = -10
-11 + 5x = 9 + -1(-10)

Multiply -1 * -10
-11 + 5x = 9 + 10

Combine like terms: 9 + 10 = 19
-11 + 5x = 19

Solving
-11 + 5x = 19

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 5x = 19 + 11

Combine like terms: -11 + 11 = 0
0 + 5x = 19 + 11
5x = 19 + 11

Combine like terms: 19 + 11 = 30
5x = 30

Divide each side by '5'.
x = 6

Simplifying
x = 6

See similar equations:

| 2r^3-3r^2=32r-48 | | 4x-9=24-3 | | 3/5x-10=-1 | | 4x-6(2x+3)=-2 | | 18.9=23.9 | | 36/60=45/x | | 37=32-2c | | 13.78-.8a=0 | | 16=8(x-1)-8 | | x/7-5/4=x/14-1/28 | | 19z-18z=16+22 | | 7(m-3)-5m=2(m-10)-1 | | 1/2x27 | | 2(x+2.3)=x+6.4 | | 10+(-5)= | | 9x+3-6x-5=19 | | y+46=28 | | 3a+5=15 | | 3(x+4)+6=27 | | 1.1+8.8=5.9a-4.9a+4.9 | | z+3=5 | | x^2-12x+100=0 | | 6(3n+3)=6(9n+3)+3 | | 2z/5-x2=40 | | y=6x^3-48 | | x^2/6-x/2-3=0 | | y=3/7(x-7)+2 | | 7x-12x*5=-45+15 | | x-5.5=5.6 | | -0.6x-10=0.3 | | 20-4[c-3-6(2c+3)]=5(3c-2)-[2(7c-8)-4c+7] | | 0.9x-4.2=3.0 |

Equations solver categories